2021
DOI: 10.1021/acsmaterialslett.1c00490
|View full text |Cite
|
Sign up to set email alerts
|

Polyolefins and Polystyrene as Chemical Resources for a Sustainable Future: Challenges, Advances, and Prospects

Abstract: Nonbiodegradable plastics with inert and saturated C−C backbones comprise the majority of global annual plastics produced, including the ubiquitous polyolefins (polyethylene and polypropylene) and polystyrene. Unlike polymers with cleavable bonds, such as polyesters, polyurethanes, and polycarbonates, these inert plastics are the most challenging to upcycle and cannot be easily broken down by chemical or enzymatic means. Thus, they mostly end up in landfills or are incinerated to produce copious amounts of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 123 publications
(228 reference statements)
0
69
0
2
Order By: Relevance
“…Different from the primary recycling, secondary recycling refers to mechanical recycling in which the recovered wastes are utilized to construct other products for different applications, achieving open-loop recycling. 16 The waste polyolefins always undergo the following steps 17 : (1) separation and sorting on the basis of the size, shape, density, and other properties; (2) baling and transport; (3) washing to remove the contaminants; (4) grinding to form the plastic flakes; (5) compounding and pelletizing to meet the converter standard; and (6) extrusion. In the extrusion process, the polymers can be plasticized or softened by the heat and rotating screws, followed by the production of fixed cross-section extrudate via the temperature-controlled barrel sections.…”
Section: Recycling Approach Of Waste Polyolefinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Different from the primary recycling, secondary recycling refers to mechanical recycling in which the recovered wastes are utilized to construct other products for different applications, achieving open-loop recycling. 16 The waste polyolefins always undergo the following steps 17 : (1) separation and sorting on the basis of the size, shape, density, and other properties; (2) baling and transport; (3) washing to remove the contaminants; (4) grinding to form the plastic flakes; (5) compounding and pelletizing to meet the converter standard; and (6) extrusion. In the extrusion process, the polymers can be plasticized or softened by the heat and rotating screws, followed by the production of fixed cross-section extrudate via the temperature-controlled barrel sections.…”
Section: Recycling Approach Of Waste Polyolefinsmentioning
confidence: 99%
“…3,4 Present statistics and estimations indicated that the global plastic production reached about 360 million tons (Mt) in 2019, and the annual output of plastics by 2050 would exceed 500 Mt. 5 However, the service lives of most plastics are limited and usually below 1 month due to their disposable applications. This phenomenon leads to the excessive discharge of waste plastics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…to these polymers via chemical methods (e.g., oxidation, halogenation, esterification, metathesis etc.) [896][897] as depicted in Figure 49. The products include polymers with new properties, 898 liquid fuels, 899 waxes, 900 and platform molecules.…”
Section: Functionalization Of Polymersmentioning
confidence: 99%